Implementation of Conventional Motorcycle Conversion into Electric Motorcycle Using BLDC Motor and LiFePO4 Battery - Ramadhan, Miftahuddin; Putra, Dwi Sudarno; Purwanto, Wawan; Setiawan, M. Yasep; Muslikhin, Muslikhin (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
The high level of air pollution is partly triggered by emissions from fossil-fuel-powered vehicles. Therefore, the presence of environmentally friendly vehicles is greatly needed. On the other hand, the availability of conventional vehicles cannot be immediately eliminated. One alternative is to convert conventional vehicles into electric vehicles. This study aims to assess and implement the process of converting conventional motorcycles into electric motorcycles as a more environmentally friendly transportation solution. The main components used are several parts from conventional motorcycles, a BLDC electric motor as the main drive, an electronic control unit, and a LiFePO4 battery as the energy source. The study was conducted using the R&D method. The result of the study is the creation of a converted electric motorcycle with a 3KW BLDC hub motor and a 48V 15 Ah LiFePO4 battery, with an average range of 30 km per full battery charge and a maximum speed of 56.7 km/h. Tingginya polusi udara salah satunya dipicu oleh emisi gas buang kendaraan berbahan bakar fosil. Oleh karenanya kehadiran akan kendaraan yang ramah lingkungan sangat dibutuhkan. Di lain sisi, ketersediaan kendaraan konvensional tidak bisa langsung dihilangkan. Salasatu alternatifnya adalah melakukan konversi dari kendaraan konvensional menjadi kendaraan listrik. Penelitian ini bertujuan untuk mengkaji dan mengimplementasikan proses konversi sepeda motor konvensional menjadi sepeda motor listrik sebagai solusi transportasi yang lebih ramah lingkungan. Komponen utama yang digunakan adalah beberapa part dari sepeda motor konvensional, motor listrik BLDC sebagai penggerak utama, unit pengendali elektronik dan baterai jenis LiFePO4 sebagai sumber energi. Penelitian dilakukan dengan metode R & D. Hasil penelitian berupa terwujudnya sebuah sepeda motor listrik konversi dengan motor hub BLDC 3KW dan baterai Lifepo4 48V 15 Ah, dengan kemampuan jarak tempuh rata-rata 30 Km sekali pengisian full baterai dan kecepatan maksimum 56,7 Km/Jam.